Epistolary Dialogue between Zofia Kossak and Jan Dobraczyński. Forms of Address and Letter Signatures - Nowak, Małgorzata; Truszkowski, Artur (Respectus Philologicus, 2024)
The epistolary discourse between Zofia Kossak and Jan Dobraczyński, spanning from 1947–1968, proves the dynamic nature of their relationship. The study focuses on the forms of address and epistolary signatures in their correspondence. In addition to the opening and closing formulas, the forms of address attested in the epistolary corpus under analysis were also analysed. As formal exponents of the bond and of the signalled sender-receiver attitude, forms of address differed. Dobraczyński’s use of forms of address was fixed and conventional, with little variation in his signatures. Conversely, Kossak was more spontaneous in both respects. Her forms of address featured nominalised variants of conventional adjectives like dear and beloved, used singularly or in a syntagmatic series, and complemented by the addressee’s name in the main, diminutive or hypocoristic form. Some cases were colloquial and humorous phrases with the lexeme dad and chap/man. Still other forms included occasional, allusive lexemes, resultant from the subject matter of the letters. Beyond fulfilling the phatic function typical of such correspondence, these forms of address also served denotative and expressive purposes.